Nowcashing : Using Daily Fiscal Data for Real-Time Macroeconomic Analysis - Misch, Florian; Kejji, Lamya; Olden, Brian; Poplawski Ribeiro, Marcos (Washington, D.C. : International Monetary Fund, 2017)
Traditionally, fiscal data for policy analysis are derived from official reports that, depending on the country, are published either monthly, quarterly or annually, often with significant time lags. However, innovations in digitalization of government payments and accounting systems mean that real-time daily fiscal data exist in many countries. In this paper, we argue that these data contain valuable, but underutilized and underexploited information. Possible uses include (i) realtime fiscal surveillance which allows for much more timely responses to emerging signs of fiscal stress, and (ii) nowcasting economic activity, which is especially useful in countries where higher frequency GDP statistics are unavailable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet